(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Being an important factor in ensuring the solvency of banks, it is a necessary condition for ensuring the continuity of payments made in the country’s economy. The article identifies current problems related to liquidity and solvency and develops scientific proposals aimed at solving them.